Epidermal growth factor receptor‐targeted molecular imaging of colorectal tumors: Detection and treatment evaluation of tumors in animal models. Issue 6 (20th May 2019) - Miyamoto, Yoshihiko; Muguruma, Naoki; Fujimoto, Shota; Okada, Yasuyuki; Kida, Yoshifumi; Nakamura, Fumika; Tanaka, Kumiko; Nakagawa, Tadahiko; Kitamura, Shinji; Okamoto, Koichi; Miyamoto, Hiroshi; Sato, Yasushi; et al.
Abstract: To overcome the problem of overlooking colorectal tumors, a new and highly sensitive modality of colonoscopy is needed. Moreover, it is also important to establish a new modality to evaluate viable tumor volume in primary lesions of colorectal cancer (CRC) during chemotherapy. Therefore, we carried out molecular imaging of colorectal tumors targeting epidermal growth factor receptor (EGFR), which is highly expressed on tumor cells, for evaluating chemotherapeutic efficacy and for endoscopic detection of colorectal adenomas. We first attempted to image five CRC cell lines with various levels of EGFR expression using an Alexa Fluor‐labeled anti‐EGFR monoclonal antibody (AF‐EGFR‐Ab). A strong fluorescence signal was observed in the cells depending on the level of EGFR expression. When nude mice xenografted with LIM1215 CRC cells, which highly express EGFR, were i.v. injected with AF‐EGFR‐Ab, a strong fluorescence signal appeared in the tumor with a high signal to noise ratio, peaking at 48 hours after injection and then gradually decreasing, as shown using an IVIS Spectrum system. When the xenografted mice were treated with 5‐fluorouracil, fluorescence intensity in the tumor decreased in proportion to the viable tumor cell volume. Moreover, when the colorectum of azoxymethane‐treated rats was observed using a thin fluorescent endoscope with AF‐EGFR‐Ab, all 10 small colorectal adenomas (≤3 mm) were detected with a clear fluorescence signal. These preliminary results of animal experiments suggest that EGFR‐targeted fluorescent molecular imaging may be useful for quantitatively evaluating cell viability in CRC during chemotherapy, and also for detecting small adenomas using a fluorescent endoscope. Abstract : Molecular imaging targeting epidermal growth factor receptor (EGFR) showed utility for evaluating therapeutic efficacy, as indicated by viable cell volume, more accurately than tumor size. This EGFR imaging method was also useful in detecting colorectal adenoma in rat colorectum. This imaging method may lead to advancements in early detection and improved diagnosis of colorectal tumors, as well as therapeutic evaluation of colorectal cancer.